Mining company governance and the spectre of environmental prosecutions: Is there any deterrent effect? - Monoke, Kwena Martha (University of the Witwatersrand, Johannesburg, 2024)
South Africa has developed good environmental legislation, but compliance with these laws is still a challenge (Linde, 2006; Skosana, 2019). According to (Digby, 2016), the South African mining industry has a notorious legacy of inadequate rehabilitation and partially closed mine sites. Mining company directors are the custodians of the company governance and have a duty to ensure compliance with all relevant mining legislation (Bezuidenhout, 2018). Their failure to comply with the law triggers, in many instances, a criminal infraction. All South African environmental legislation relies on criminal penalties to enforce its prescriptions and to punish its offenders (Murombo and Munyuki, 2019). South Africa has strict criminal sanctions for environmental noncompliance and degradation (Truter, 2014). The awareness of South Africans with regards to environmental crimes has increased due to initiatives such as the annual National Environmental Compliance and Enforcement Report, and online judgment archives such as the South African Freedom of Legal Information Institute (SAFLII) and Juta Law (Department of Forestry, Fisheries and the Environment, 2023a). The State v Blue Platinum Ventures and Mr Maponya case was used as a case study. This study seeks to investigate whether the threat of environmental prosecution influenced the mining company governance and its director and whether it had any deterrent effect on the company’s commission of environmental crimes. A qualitative case study approach was undertaken. Several documentary sources of information were relied on for the analyses of the Blue Platinum case and interviews were conducted to fill in the gaps from the data analyses. It was determined that the rule of law was being put into practice and that the community had received justice because rehabilitation was conducted and it addressed their concerns. The Blue Platinum Ventures and Mr Maponya case has had a deterrent effect on the company itself and Mr Maponya.
A research report submitted in partial fulfilment of the requirements for the Degree of Master of Science in Global Change Studies, to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: Deterrence; Environmental prosecutions; Criminal prosecutions; UCTD; SDG-15: Life on land; SDG-9: Industry, innovation and infrastructure